Badanie EEG u dzieci przyjętych z powodu pierwszego epizodu drgawek niezwiązanych z gorączką w Ahvaz, w południowo-zachodnim Iranie - Momen, Ali Akbar; Davoodzadeh, Hannaneh; Morvaridnejad, Maryam (Neuropsychiatria i Neuropsychologia/Neuropsychiatry and Neuropsychology, 2017)
Introduction : Seizures are one of the most common disorders in children. EEG is the most important tool in diagnosis and follow-up in patients with seizures. To diagnose which children might experience recurring seizures, EEG can be helpful. This research was conducted to investigate risk factors of seizure recurrence in non-febrile seizures. Methods: In this descriptive study, EEGs were obtained from all children referred to Ahvaz Golestan hospital following an initial, unprovoked, and untreated seizure. Data were analysed by SPSS version 20, and P < 0.05 was considered as significant. Results : Thirty-two children aged 4 months to 14 years participated. The patients mean age was 2.75 years. Eighteen cases (56.25%) were male and 14 (43.75%) were female. Twenty-seven of the cases had normal birth weight and five had low birth weight. Of the 32 children evaluated, five children (15.62%) had developmental retardation status. The average duration of seizures was 155 seconds. A positive family history of seizures was reported in 13 (40.62%) children. EEG findings were abnormal in 19 patients (59.37%), and they were normal in 13 patients (40.63%), in which three forms were seen: focal spikes in 10 patients (31.25%), focal spikes with slow waves in six patients (18.75%), and general spikes with slow waves in three patients (9.37%). Conclusion : This study revealed a significant correlation between the presence of a family history of seizures and developmental delays in children with first non-febrile seizures and abnormal EEG. It is suggested that EEG be conducted on the first non-febrile seizure, especially in children with a positive family history of seizures or developmental delay.